Hybrid systems of Graphene and h-BN - Chinchay, Carlos Alberto León (2017)
This thesis is devoted to a theoretical study on isolated graphene nanoribbons, isolated hexagonal boron nitrite systems, and other hybrid configurations mixing both kinds of nanoribbon systems. First we analyze the main aspects of the electronic properties of graphene and h-BN nanoribbons including the possibility of getting half metallicity under the presence of external electric fields Simple tight binding approximations were used as a starting point and real-space normalization schemes are followed to derive Green’s functions, local density of states, and also some transport properties such as the conductance. We then construct a hybrid graphene-BN nanoribbon system, using a Hubbard model Hamiltonian within a mean field approximation. Due to different electronegativities of the boron and nitrogen atoms, an electric field is induced across the zigzag graphene strip, breaking the spin degeneracy of the electronic band structure. Optimal tight-binding parameters are found from DFT calculations carried on the Quantum Espresso code, based on density-functional theory, plane waves and pseudopotentials. Edge potentials were proposed as corrections for on-site energies, and to investigate how the BN-graphene nanoribbon interfaces are perturbed. We also study the effects of impurities along the graphene nanoribbon and at the interface regions. We found that energy gap sizes may be properly engineered by controlling the spatial doping process and, moreover, that binding energy impurity calculations may be used to study impurity diffusion processes along the mixed nanoribbons. We show that substitutional impurities may enhance half-metallic response. Different impurity configurations and the corresponding energy stabilities were studied. In a second study, we consider deformations in graphene nanoribbons that may be considered as central elements in the novel field of straintronics. Various strain geometries have been proposed to produce specific properties, but their experimental realization has been limited. Because strained folds can be engineered on graphene samples on appropriate substrates, we study their effects on graphene transport properties and on the local density of states. Conductance calculations reveal extra channels within the energy range corresponding to the first conductance plateau for the undeformed ribbon, in addition to those due to edge states. Band structure calculations confirm that these channels originate from higher energy states that localize along the strained fold-like area. Furthermore, states with the same velocity show real spatial valley polarization, i.e., a current injected along the deformed structure will be split into two currents: one along the center of the strained fold constituted by states from one valley, and another running at its sides with contributions from states of the other valley. In addition to exhibiting sublat- tice symmetry breaking, these states are valley polarized, with quasiballistic properties in smooth disorder potentials. These findings could be tested in properly engineered experimental settings. We also investigate the effects of Coulomb correlations on the half metallicity of graphene nanoribbons when mechanical deformations like fold perturbations are taken into account.